2014
DOI: 10.2214/ajr.13.11816
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Detection Using Double Reading of Unenhanced MRI Including T1-Weighted, T2-Weighted STIR, and Diffusion-Weighted Imaging: A Proof of Concept Study

Abstract: An unenhanced breast MRI protocol composed of T1-weighted gradient echo, T2-weighted STIR, and echo-planar DWI enabled breast cancer detection with sensitivity of 76-78% and specificity of 90% without a gain in sensitivity from double reading.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
63
2
9

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 38 publications
3
63
2
9
Order By: Relevance
“…The overall reader sensitivities of 86% and 89% for the abbreviated 1 and 2 protocols, respectively, and 95% for the full protocol were comparable to the 90% sensitivity of breast MRI generally reported by multiple prior investigators (4,6,7). The results of this pilot study contribute to the growing body of data that suggest that shortened breast MRI protocols may become a viable clinical option for screening (28)(29)(30)(31). Kuhl et al (28) recently demonstrated excellent sensitivity (100%) and specificity (94.3%) using an abbreviated protocol that included only a T1-weighted precontrast and a single postcontrast sequence, similar to our abbreviated 1 protocol.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The overall reader sensitivities of 86% and 89% for the abbreviated 1 and 2 protocols, respectively, and 95% for the full protocol were comparable to the 90% sensitivity of breast MRI generally reported by multiple prior investigators (4,6,7). The results of this pilot study contribute to the growing body of data that suggest that shortened breast MRI protocols may become a viable clinical option for screening (28)(29)(30)(31). Kuhl et al (28) recently demonstrated excellent sensitivity (100%) and specificity (94.3%) using an abbreviated protocol that included only a T1-weighted precontrast and a single postcontrast sequence, similar to our abbreviated 1 protocol.…”
Section: Discussionsupporting
confidence: 70%
“…In another study, Mango et al (31) showed that in patients with biopsy-proven cancer, a protocol using only precontrast and postcontrast T1-weighted sequence could be used to accurately localize unicentric tumors with a sensitivity of 96%. Additional research has been directed toward shortening the acquisition time of postcontrast breast MRI sequences by replacing standard dynamic postcontrast sequences with ultrafast time-resolved angiography (29) or diffusion-weighted imaging (30). Reducing breast MRI scan times could address several challenges in current breast MRI screening practices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method was previously used in some experimental clinical and reader studies and found to be useful for the diagnosis of breast cancer (24)(25)(26)(27). Lastly, Trimboli et al (28) reported 78% sensitivity and 87% specificity for breast cancer detection with unenhanced MRI of 67 women.…”
Section: Discussionmentioning
confidence: 98%
“…Breast cancer is the most common cancer detected in Chinese women in the past 20 years; the incidence rate is rising, and therefore the early detection, diagnosis and treatment are important for the survival and life quality of these patients (1)(2)(3)(4)(5)(6). When assessing the tumorigenic process of breast cancer, the World Health Organization (WHO) histopathological grade is an important indicator that can be used to evaluate the malignant behavior and prognosis of breast cancer.…”
Section: Introductionmentioning
confidence: 99%